Perancangan Sistem Navigasi Terestrial Untuk Pesawat Udara Wing in Surface Effect 8 Penumpang (Wise-8) - Setiyo Prabowo, Achmad (Politeknik Penerbangan Makassar, 2019)
Wing in Surface Effect (WiSE) aircraft are airplanes that fly-cruises only a few meters above sea level, using surface effects. WiSE-8 is a transportation facility that will be operated in sea waters in several regions in Indonesia. If it refers to the rules of the air transportation system issued by the International Civil Aviation Organization (ICAO) and the rules of the sea transportation system of the International Maritime Organization (IMO), the supporting equipment that must be available is radio communication and navigation equipment in a predetermined frequency range. One of the navigation systems that WiSE will use is a satellite-based navigation system, the Global Positioning System (GPS). At present, the GPS can still be used freely and only requires a GPS receiver. If one day its use will be limited it will also lose the freedom of the use of the GPS. Therefore this research is focused on the application of navigation systems that will be used by WiSE-8 based terrestrial navigation equipment. The terrestrial navigation system for WiSE-8 is using the Directional Finder (DF) system. This system provides information in the form of bearings relative to a radio station transmitting on land, with the accuracy of this system is 1o. So the level of error estimation of the smallest position on the Dumai-Batam route using 2 signals of a radius of 1.4037 NM. The estimated error rate of the position will be even greater if the target receives only one beam signal